Randomized controlled study of the efficacy and safety of continuous saline bladder irrigation after transurethral resection for the treatment of non‐muscle‐invasive bladder cancer. (18th August 2016) - Onishi, Takehisa; Sugino, Yusuke; Shibahara, Takuji; Masui, Satoru; Yabana, Tadashi; Sasaki, Takeshi
Abstract : Objective: To evaluate the efficacy and safety of continuous saline bladder irrigation (CSBI) after transurethral resection of bladder tumour (TURBT) in patients with low‐ to intermediate‐risk non‐muscle invasive bladder cancer (NMIBC). Patients and Methods: In this prospective randomized study, 250 patients with primary low‐ to intermediate‐risk tumours were enrolled. Patients were randomly allocated to receive CSBI (2 000 mL/h for the first 1 h, then 1 000 mL/h for 2 h, followed by 500 mL/h for 15 h) or a single immediate instillation of mitomycin C (MMC) after TURBT. The primary endpoint was recurrence‐free survival, and secondary endpoints were progression‐free survival and adverse events. Results: A total of 227 patients (114 in the CSBI group and 113 in MMC group) remained for analysis after exclusion criteria had been applied. The median follow‐up period was 37 months. No significant differences in patient characteristics were observed between the groups. The 5‐year recurrence‐free rates for CSBI and MMC were 62.6% (95% confidence interval [CI] 0.49–0.73) and 70.4% (95% CI 0.59–0.78), respectively. Kaplan–Meier analysis of recurrence‐free survival did not show any significant differences between the groups (log‐rank test P = 0.53). Furthermore, there were no significant differences between the groups in terms of tumour progression rate and the median time to first recurrence. The incidence of adverse events was significantly lower in the CSBI group. Conclusions: The results show that CSBI after TURBT may be a treatment option for patients with low‐ to intermediate‐risk NMIBC in terms of its prophylactic effect and safety.